Conversion of Bengali speech to text using long short-term memory(LSTM) - Chowdhury, Mohammad Fahim; Sultana, Zakia; Jahan, Nusrat; Alavi, Safkat Hasin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.